Essays in applied microeconomics - Kleis, Mischa (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
The first essay studies the effects of access to assisted reproductive technologies (ARTs) on fertility and labor market outcomes. Drawing on quasi-experimental variation in expected costs for ARTs and data from the German Microcensus, I find a weakly significant decrease in the probability to give birth for German women aged 30 to 34 in former East-Germany, while women's labor force participation remains unaffected. This result is in line with the hypothesis that access to infertility treatments may ease women's perception of the career-family tradeoff and may motivate them to postpone motherhood. For West-Germany, the findings suggest that while there is no significant impact of the policy intervention on German women?s fertility behavior, it motivates women aged 30 to 34 to withdraw from the labor market - albeit the effect is only marginally significant. This result does not align with the theoretical considerations. In combination with the results on males, these observations challenge the validity of the obtained estimates in terms of reflecting the true effects of subsidizing ARTs on German women. The second essay examines the impact of stricter regulation of a single input to the production of child care on the structural quality of the child care environment and children's development. Using a novel recording of legislative changes to maximum child-to-staff ratios (CSR) in early child care (ECC) "care for children aged 0-2" I find that the CSR reforms have no statistically significant effect on the observed CSR. Further, my analysis uncovers no impact of the stricter regulations on other aspects of structural quality in child care, such as the qualification of pedagogical staff or the degree of staff fluctuation. Accordingly, I cannot confirm the presence of a child care market where regulations are enforced and binding. These results also suggest that child care providers refrain from engaging in cost-saving input substitution. Further, I show that the CSR reforms have no significant effect on children's development. Hence, the essay hints at a potentially limited scope of such policies to improve children's development. The third essay contributes to the literature on sociodemographic segregation in child care participation and social mobility. Relying on my compilation of regional reforms to legislated CSR in ECC and representative survey data on ECC enrollment, I study the impact of increased minimum quality standards for the provision of child care on sociodemographic enrollment gaps in ECC. I find that increased minimum standards in ECC had no significant effect on enrollment gaps by parental education and migration background. This suggests that such a policy may not be an appropriate measure to reduce segregation in child care enrollment and to improve social mobility.
APPROVED
Keywords: fertility; career-family tradeoff; child care; child development; family background; regulation; quality; infertility; labor force participation